INHABITANT’S SENSE OF PLACE IN THE CONTEXT OF TOURISM KAMPUNG - Annisa Nur Ramadhani; Muhammad Faqih; Arina Hayati (Journal of Architecture&ENVIRONMENT, 2018)
Kampung improvement program in Surabaya is considered successful in enhancing the qualty of housing and settlement-based on sustainable development. Recently, several kampungs develop based on tourism thematic (Thematic Tourism Kampung Programme) that adopts cultural conservation value both tangible and intangible. The development of this tourism kampung has a positive purpose to improve the socio-economic prosperity of its people. On the other hand, there is a change of function and meaning of the kampung from an urban kampung to a tourism kampung. It means that the kampung settlement becomes more accessible to the public visitors, ie tourists who want to visit and feel the experience of place within the kampung. In this case, the changes that occur have affect both kampung’s dimensions physically and non-physically, because sense of place is closely related to the level of community participation and the sustainability of a development. This paper aims to enrich the model of sense of place in the smaller context which is tourism kampung development in developing county through an approach based on an in-depth literature review of relevant studies and official documents of institutions. The main dimensions and elements have been identified to measure community’s sense of place level in tourism kampung. The different theories of sense of place are reviewed to show the need of a shared definition of what constitutes a sense of place, its features, and its performance in the specific context (tourism kampung). The result of this research explain that variables of sense of place consist of form, activity, and meaning which has sub variable namely place attachment and bonding. Furthermore, the identified variables will be used to form a questionaire in the next sense of place study especially in the tourism kampung context.